Improving Students’ English Pronunciation Competence by Using Shadowing Technique - Utami, Henny Septia; Morganna, Ruly (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study used classroom action research at SMPN 1 Curup Timur in Bengkulu, using the shadowing technique to assist students in resolving their English pronunciation issues. As participants, 25 ninth-grade students were involved. The shadowing technique was carried out in two cycles, with each cycle consisting of three meetings. Two meetings were scheduled for the shadowing learning processes, with the third serving as a post-test. Observations and tests were used to collect data. The data were analyzed both qualitatively and quantitatively. This study uncovered two sets of data. First, for each meeting in each cycle, the process of learning English pronunciation using shadowing techniques included ten stages that included listening, listening while marking, mumbling, parallel reading, comprehending meanings, shadowing prosody sounds, recording, listening, and making comparisons, reviewing, and reflecting. Second, the shadowing technique was effective in improving students' English pronunciation skills. In cycle one, this technique was capable of improving English pronunciation indicators such as phonemes, sound combinations, and sound linkage. Following that, in cycle two, this technique could improve four other indicators: allophones, stress, rhythm and pitch, and intonation.